Development of Web Based Teaching Materials on Environmental History - Wahyudi, Deny Yudo; Wijaya, Daya Negri; Pratama, Andhika Yudha; Utari, Shela Dwi (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This research aims to develop website-based teaching materials with environmental history material integrated with eco-pedagogy. This is an effort to provide new insight for undergraduate History Education and Teacher Professional Education (PPG) undergraduate students at the State University of Malang majoring in history regarding environmental history and eco pedagogy. This research uses Borg and Gall's development research method, which is adjusted to the research conditions in the field. The data analysis technique was carried out descriptively, while the questionnaire data was calculated qualitatively and quantitatively for the student respondent test. The results showed that ecohistory scored 82.89% for website-based teaching materials. This shows that this teaching material is feasible and can be used efficiently. The success of this trial is a good indicator of its potential future application in a classroom learning environment.